Deutsche und sowjetische Gesellschaften im ersten Nachkriegsjahrzehnt Traumata und Hoffnungen - Cubar'jan, Aleksandr O.; Wirsching, Andreas (Mitteilungen der Gemeinsamen Kommission für die Erforschung der jüngeren Geschichte der deutsch-russischen Beziehungen, 2021)
This 9th bilingual volume of the Joint Research Committee on the Contemporary History of German-Russian Relations documents the 2016 colloquium "German and Soviet Societies in the First Post-War Decade: Traumas and Hopes." In the second part, young historians from Russia and Germany present "New Perspectives on German-Russian Relations and Historical Interconnections in the 19th and 20th Centuries in a Global Context."